Dielectric relaxations of nanocomposites composed of HEUR polymers and magnetite nanoparticles. (25th July 2016) - Campanella, A.; Brás, A.; Raftopoulos, K.N.; Papadakis, C.M.; Vassiliadou, O.; Kyritsis, A.; Appavou, M.S.; Müller-Buschbaum, P.; Frielinghaus, H.
Abstract: We investigate the dynamics of nanocomposites composed of hydrophobically modified ethoxylated urethanes (HEUR) and magnetite nanoparticles (MNPs) as dry films. We employed dielectric relaxation spectroscopy (DRS) in combination with differential scanning calorimetry (DSC) and thermally stimulated depolarization currents (TSDC). The three techniques reveal a strong heterogeneity of the matrix of the nanocomposites, consisting of (i) a crystalline poly(ethyleneoxide) PEO bulk phase, (ii) an amorphous PEO portion, and (iii) small PEO crystallites which experience different constraints than the PEO bulk phase. TSDC and DRS reveal a very high direct current (DC)-conductivity of the pure matrix, which increases with MNPs concentration. The increase of the DC-conductivity is not related to an increase of the segmental mobility, but most likely to the change of the morphology of the hydrophobic domains of the polymer matrix, due to the formation of large MNPs clusters. Indeed, the MNPs neither influence the segmental dynamics of the polymer nor the phase behavior of the polymer matrix. The addition of MNPs slightly increases the activation energy related to the γ -relaxation of the polymer. This effect might be related to the changes in nano-morphology as demonstrated by the slight increase of the degree of crystallinity. The analysis of the DRS data with the electrical modulus M″(ω) and the derivative ε″ der formalism allow us to identify a low-frequency process in addition to the conductivity relaxation. This low-frequency dispersion is also revealed by TSDC. It is most likely related to the Maxwell-Wagner-Sillars relaxation, which typically occurs in systems which feature phase separation. The detailed investigation of the dielectric properties of these novel nanocomposites with increasing MNPs concentration will be useful for their practical application, for example as absorbers of electromagnetic waves. Graphical abstract: Highlights: The dynamics and the thermal behavior of HEUR-MNPs nanocomposites are investigated. The HEUR matrix consists of i) amorphous PEO ii) crystalline PEO iii) small PEO crystallites The MWS relaxation, typical of micro-phase separated systems, was found. The MNPs do not influence the dynamic–glass transition of the amorphous PEO portion. The addition of the MNPs leads to a high increase of the dc-conductivity.